Triple phase computed tomography of the pancreas in healthy cats. Issue 2 (28th November 2017) - Secrest, Scott; Sharma, Ajay; Bugbee, Andrew
Abstract: While the availability and use of computed tomography (CT) continues to grow, no study has described the size and multiphase CT appearance of the normal feline pancreas. This information is important to not only allow more accurate identification and differentiation of disease, but it may also be useful in assessing pancreatic function. In this prospective analytical study, we described a triple phase CT protocol of the pancreas for use in sedated cats and the attenuation, enhancement pattern, size, and volume of the pancreas for a group of healthy cats. Fifteen healthy cats were enrolled in the study and a standardized protocol for acquiring arterial, portal, and delayed phase CT images of the pancreas was developed and described. The pancreas was hypo to isoattenuating to both the liver and spleen in all phases in the majority of cats with a homogenous enhancement pattern noted in all 15. Mean pancreatic attenuation was 48, 79, 166, and 126 Hounsfield units (HU) respectively on precontrast, arterial, portal, and delayed phase images. In addition, mean height, length, and width of the left lobe of the pancreas were larger than the right lobe in all 15 cats. There were no associations between volume and volume: body weight ratio with age ( P  = 0.6518, P  = 0.6968) or sex ( P  = 0.7013, P  = 0.2043). This baseline information may be beneficial for use in future studies characterizing pancreatic disease in cats as well as future research studies evaluating pancreatic endocrine function.